2020
DOI: 10.1371/journal.pone.0227640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood lactate and perceived exertion responses in two matched time-under-tension protocols

Abstract: The aim of this study was to compare the concentration of blood lactate [bLa-] and the subjective perception of exertion of trained men in a moderate repetition protocol (MRP) versus a high repetition protocol (HRP) equated for time under tension. Methods A sample of 40 healthy young men (aged, 23.2 ± 4.0 years; height, 177.3 ± 7.0 cm; BMI, 24.3 ± 2.2) performed two sessions of 8 sets of bicep curls with a one-week recovery interval between the trials. In the HRP protocol, 20 repetitions were performed with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…With TUT matched at 36 seconds per set, Lacerda et al [91] demonstrated that faster tempo repetitions (3 seconds) increased blood lactate more than slower tempo repetitions (6 seconds). Similar results were achieved by Vargas-Molina et al [92] when TUT was matched at 60 seconds per set. This study improved upon the methods of Lacerda et al [91] because effort was matched between conditions as every set was performed to momentary muscular failure.…”
Section: Acute Effect Of Repetition Tempo On Metabolic Stresssupporting
confidence: 87%
See 4 more Smart Citations
“…With TUT matched at 36 seconds per set, Lacerda et al [91] demonstrated that faster tempo repetitions (3 seconds) increased blood lactate more than slower tempo repetitions (6 seconds). Similar results were achieved by Vargas-Molina et al [92] when TUT was matched at 60 seconds per set. This study improved upon the methods of Lacerda et al [91] because effort was matched between conditions as every set was performed to momentary muscular failure.…”
Section: Acute Effect Of Repetition Tempo On Metabolic Stresssupporting
confidence: 87%
“…Thus, there is agreement in the current literature that metabolic stress increases with TUT [66][67][68][69][70][71]. Moreover, when TUT is matched, metabolic stress is greater under conditions where more repetitions are performed per set (e.g., 20 vs. 10 reps) and faster/ traditional tempos (e.g., 3 vs. 6 sec) are used (91,92). In the future, researchers should emulate the design of Vargas-Molina et al [92] by matching TUT and assessing the effect of several tempo schemes on a variety of exercises (i.e., single vs. multiple joint, upper vs. lower body).…”
Section: Acute Effect Of Repetition Tempo On Metabolic Stressmentioning
confidence: 65%
See 3 more Smart Citations